Recent Patents for the Motorized Spindle Preload Mechanism - Dai, Ye; Wen, Wan-Jian; Xuan, Li-Yu; Yu, Xiao-Yang; Wang, Gang (Recent Patents on Mechanical Engineering, 2021)
Background: The motorized spindle preload technology is one of the motorized spindle key technologies, and adjusting the preload according to the working conditions can effectively improve the dynamic performance of the motorized spindle and enhance the machining accuracy. Objectives: Review the preload mechanism development, introduce various preload mechanisms, and show research status in recent years. Then to explore and predict the future development of preload technology through the analysis of the overall preload mechanism. Methods: Search for different kinds of patents and literature about spindle preload structure in recent years. Through structural research and comparison with the traditional preload mechanism, to review the structure principle of various preload mechanisms at the present stage, then shown the advantages and disadvantages of each structure. Result: According to the patents and research of the preload mechanism in recent years, classification introduced the piezoelectric ceramic preload device, electromagnetic preload device, and hydraulic preload device, and so on. Introduce their advantages and existing problems in detail, then comprehensively compare the advantages and disadvantages of various mechanisms in control and mechanism. Finally, discuss the prospects and development directions of preload technology. Conclusion: With the further development of technology, high-precision products have higher requirements for machine tools, such as low latency, low heat generation, high efficiency, and long life. People use electromagnetic force, air pressure, hydraulic pressure, and other methods, to control the magnitude of the preload, maintain the performance of the motorized spindle at a high level. Compared with the traditional quantitative preload, their applicable working conditions are more extensive and accuracy is higher. However, various new preload methods still have certain shortcomings and need further improvement.
Keywords: preload